Governance with poor investor protection: evidence from top executive turnover in Italy - Volpin, Paolo F. (Journal of Financial Economics, 2002)
This paper studies the determinants of executive turnover and firm valuation as a function of ownership and control structure in Italy, a country that features low legal protection for investors, firms with controlling shareholders, and pyramidal groups. The results suggest that there is poor governance, as measured by a low sensitivity of turnover to performance and a low Q ratio, when (i) the controlling shareholders are also top executives, (ii) the control is fully in the hands of one shareholder and is not shared by a set of core shareholders, and (iii) the controlling shareholders own less than 50% of the firm's cash-flow rights.